Reduction of electricity consumption for work piece curing of hard disk drive component manufacturing - Moolla,P. (Chiang Mai University, 2015)
The aim of this research work is to reduce electricity consumption for the work piece curing step of the arm coil assembly process in the manufacturing of hard disk drives component. The research began with a study of the total electricity consumption of the production process, in order to determine the part of the process that consumes the most units of electricity. The results showed that the arm coil assembly process consumes most electricity, accounting for 53.36% of the entire process. During this production process, machines, and ovens in particular, are the main items of equipment employed. An analysis using a fish bone diagram was carried out in order to find the cause, and the results showed that electricity losses occur during the work piece curing process, before transfer to the production and adhesive curing processes, due to ineffective use of the ovens, i.e. the space is not fully utilized, there are no aids used in tandem with the product curing devices, and the ovens lose temperature during operation. This research; therefore, proposes a framework for a reduction in the use of electricity which is, first, to increase the oven conveyer speed from 170 mm per minute to 180 mm per minute, second, to design a heat-loss reduction device at the front of the oven, which in turn, can reduce temperature loss by up to 2.1 degrees Celsius, and third, to design additional curing equipment which can actually be utilized without any adverse impacts on product quality, saving approximately 90,604.80 Baht per month in electricity as a result of being able to turn off one work piece curing oven, and resulting in a payback period of 0.014 years, or approximately 6 days. This equipment can also be used with other products in the production process.